PENGEMBANGAN MEDIA RUMAH BONEKA TERHADAP PENGETAHUAN SEKS PADA ANAK USIA 5-6 TAHUN DI TK ISLAM FATIMAH KECAMATAN TAMPAN KOTA PEKANBARU - Fitri Siswanti; Ria Novianti; Rita Kurnia (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: The increasing number of cases of sexual violence is clear evidence of the lack of knowledge and understanding of children about sex education. Children should receive sex education from an early age. The development of this dollhouse media is an example to practice how to increase children's imagination, especially the knowledge of sex in children so that children can avoid sexual abuse from an early age to adulthood. The purpose of this research is to produce a suitable learning media product for children aged 5-6 years in TK Islam Fatimah, Tampan District, Pekanbaru City. The doll house media product developed aims to increase sexual knowledge in children. This research uses procedural methods according to Borg and Gall, namely research and development of R & D (Research and Development). Validation was carried out by material experts, media experts and teachers with an average score of 4.35, so it can be concluded that the development of dollhouse media is very valid, very effective, very suitable for use as a medium in the learning process.Key Words: Doll House Learning Media; Sex Knowledge; Early Childhood